2011
DOI: 10.1155/2011/154798
|View full text |Cite
|
Sign up to set email alerts
|

Reengineering Aircraft Structural Life Prediction Using a Digital Twin

Abstract: Reengineering of the aircraft structural life prediction process to fully exploit advances in very high performance digital computing is proposed. The proposed process utilizes an ultrahigh fidelity model of individual aircraft by tail number, a Digital Twin, to integrate computation of structural deflections and temperatures in response to flight conditions, with resulting local damage and material state evolution. A conceptual model of how the Digital Twin can be used for predicting the life of aircraft stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
258
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 789 publications
(331 citation statements)
references
References 41 publications
1
258
0
9
Order By: Relevance
“…If various best-physics (i.e., the most accurate, physically realistic and robust) models can be integrated with one another and with on-board sensor suites, they will form a basis for certification of vehicles by simulation and for real-time, continuous, health management of those vehicles during their missions. They will form the foundation of a Digital Twin [15][16][17][18] .…”
Section: Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…If various best-physics (i.e., the most accurate, physically realistic and robust) models can be integrated with one another and with on-board sensor suites, they will form a basis for certification of vehicles by simulation and for real-time, continuous, health management of those vehicles during their missions. They will form the foundation of a Digital Twin [15][16][17][18] .…”
Section: Conceptmentioning
confidence: 99%
“…In addition to its prominence in the recently-published roadmaps of NASA's Office of Chief Technologist (OCT) [15][16] and plans of the Air Force Research Laboratory [17][18] , the Digital Twin paradigm can provide focus to the recent advocacy of the National Science Foundation (NSF) and the National Research Council (NRC) in the areas of Simulation Based Engineering Science (SBES) 19 , Integrated Computational Materials Engineering (ICME) 20 and Materials State Awareness 21 . Many of the concepts discussed in the NSF's recommendations for SBES are pervasive throughout the themes of the Digital Twin, including, multiscale modeling of materials, dynamic simulation of sensors, and verification and validation. Because the vehicles needed for future extreme missions are unlikely to be developed using existing material forms, the design and development of new enabling (e.g., multifunctional, nanostructured, ultra-durable) materials is required and is well aligned with the NRC's ICME roadmap.…”
Section: Influence On National Goalsmentioning
confidence: 99%
“…In the longer term, it should be possible to use diagnostics of structural and materials health as part of a comprehensive philosophy of condition based management + prognosis (CBM+) [5][6][7][8][9]. In the longer term, a key goal is to pursue the concept of aircraft digital twin to represent the evolving health state of each individual asset [10].…”
Section: A Bright Future For Materials Designmentioning
confidence: 99%
“…Moreover, E. J. Tuegel and co-authors confirmed it. [2] .In their article, a model represented the idea of how a digital twin can be used to predict the lifetime of an aircraft structure and to ensure its structural integrity. In other words, the value of a digital twin is expressed in predicting local damage through the calculations of temperatures and structural deflections in conditions met during a flight.…”
Section: Introductionmentioning
confidence: 99%